The mechanism of increase of professional level of the teacher of english language of high school - Kseniya O. Kuzovenkova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Identified organizational and substantive aspects of the process enhance the professionalism of English language teacher. A list of the basic forms in which possible professional development. It is established that the basic form of increasing of professionalism is self-education. Shows the main steps of increase of professional level in their relationship with each other.